2016
DOI: 10.1149/2.0041701jes
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of FeS2and Sulfur in Li-S Battery System

Abstract: Many transition metal sulfides are electronically conductive, electrochemically active and reversible in reactions with lithium. However, the application of transition metal sulfides as sulfur cathode additives in lithium-sulfur (Li-S) batteries has not been fully explored. In this study, Pyrite (FeS 2 ) is studied as a capacity contributing conductive additive in sulfur cathode for Li-S batteries. Electrochemically discharging the S-FeS 2 composite electrodes to 1.0 V activates the FeS 2 component, contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Additionally, in terms of overpotential, N-Nb 2 O 5 exhibits the smallest overpotential, while Nb 2 O 5 exhibits the highest overpotential, which highlights the effect of surficial nanolayer. Generally, it is widely reported that a surficial nanolayer helps to minimize the excess free energy and interfacial energy [42,47] and it has been further confirmed that such surficial films reduce the polarization at the interface, [48] which then also helps to lower the overpotential. Similar trend was also shown in the previous literature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, in terms of overpotential, N-Nb 2 O 5 exhibits the smallest overpotential, while Nb 2 O 5 exhibits the highest overpotential, which highlights the effect of surficial nanolayer. Generally, it is widely reported that a surficial nanolayer helps to minimize the excess free energy and interfacial energy [42,47] and it has been further confirmed that such surficial films reduce the polarization at the interface, [48] which then also helps to lower the overpotential. Similar trend was also shown in the previous literature.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, it is interesting to note that N-Nb 2 O 5 shows minimal contact resistance but has higher charge transfer resistance compared with Nb 2 O 5 . The minimal contact resistance of N-Nb 2 O 5 is based on the previous claim [48] that surficial nanolayer/film helps to reduce the polarization at the interface, resulting in decreased contact resistance. On the other hand, as for the charge transfer of electrons, electron transport pathway is increased for N-Nb 2 O 5 with the creation of additional nanolayer, making it more difficult for electrons to transport to Nb 2 O 5 .…”
Section: Resultsmentioning
confidence: 99%
“…[3] Additionally, the degradation of anode and volume changes of sulfur species during reaction also undermine the electrochemical stability and cycle life of Li-S batteries, challenging the practical use of Li-S technology. [27] For instance, cobalt disulfide (CoS 2 ), [21] titanium disulfide (TiS 2 ), [28,29] and iron disulfide (FeS 2 ) [30] have been applied as sulfur hosts and have been demonstrated with a strong chemical interaction capability toward migrating polysulfides. [17][18][19][20] In view of cathode modification, it has been demonstrated that nonpolar carbon matrix with only physical polysulfide confinement may not be enough for high-loading cell performance during long cycle life.…”
mentioning
confidence: 99%
“…To evaluate comparable end points, the testing process follows a specific pattern during the data collection, as shown in the left side of the figure. The increase, decrease, and stabilization of the end discharge capacity points observed during the first 15 cycles can be attributed to the conditioning of the half-cells, a period that occurs after the electrolyte penetrates the electrode [17]. This increases the contact area between the electrode, electrolyte, and Cu foil, which yields an increment in the capacity.…”
Section: Numerical Analysis Evaluation Over the Lifetime Of Thementioning
confidence: 95%